An analysis of the anti-avoidance provisions contained in the South African Income Tax Act - Erasmus, Sean Fouracres (Department of Commercial Law, 2023)
The South African Income Tax Act No 58 of 1962 contains a number of specific as well as general anti-avoidance provisions. This dissertation places its main emphasis of focus on-the general anti-avoidance provisors contained in section 103 of the Act